Особливості сучасних вебзастосунків для бронювання квитків на громадський транспорт - Чорна, М. К. (ХНУРЕ, 2025)
This work is dedicated to modern web applications for booking tickets on public transport. It explores current problems that users may encounter when purchasing tickets, particularly limited functionality and an inconvenient interface. Examples of popular applications in both Ukraine and Europe are provided. One informational tool is examined in detail, highlighting its advantages and disadvantages in use, as well as emphasizing additional features that distinguish it from other applications. The focus is placed on potential improvements in booking tools to enhance the user experience.
Keywords: бронювання квитків; громадський транспорт